Crystal structure, spectroscopic characterization and Hirshfeld surface analysis of aquadichlorido{N- [(pyridin-2-yl)methylidene]aniline}copper(II) monohydrate - Molano, Miguel F. (2020)
The reaction of N-phenyl-1-(pyridin-2-yl)methanimine with copper chloride dihydrate produced the title neutral complex, [CuCl2(C12H10N2)(H2O)]·H2O. The CuII ion is five-coordinated in a distorted square-pyramidal geometry, in which the two N atoms of the bidentate Schiff base, as well as one chloro and a water molecule, form the irregular base of the pyramidal structure. Meanwhile, the apical chloride ligand interacts through a strong hydrogen bond with a water molecule of crystallization. In the crystal, molecules are arranged in pairs, forming a stacking of symmetrical cyclic dimers that interact in turn through strong hydrogen bonds between the chloride ligands and both the coordinated and the crystallization water molecules. The molecular and electronic structures of the complex were also studied in detail using EPR (continuous and pulsed), FT–IR and Raman spectroscopy, as well as magnetization measurements. Likewise, Hirshfeld surface analysis was used to investigate the intermolecular interactions in the crystal packing.